İşe İade İlâmlarının İcrasında Kesinleşme Şartı - (:unkn) unknown (My University, 2020)
eçerli neden olmadan iş sözleşmesi feshedilen işçi, iş iade davası açmak ve ilgili haklarını hükme bağlatmak hakkına sahiptir. İşe iade ilâmı, yeni bir iş sözleşmesi kurulmasıyla aynı hukukî sonuçları doğurur. İşçi davayı kazanırsa işe iade ilâmındaki fer’ilerin ilâm borçlusu tarafından yerine getirilme-si için icra dairesine başvurabilir. Hukuk Muhake-meleri Kanunu’na göre istinaf yoluna başvurma, kararın icrasını durdurmaz. İcra ve İflas Kanunu’nun icranın geri bırakılmasıyla ilgili 36. maddesi hükmü saklıdır (HMK m. 350/1). Kişiler hukuku, aile huku-ku ve taşınmaz mal ile ilgili ayni haklara ilişkin ka-rarlar kesinleşmedikçe yerine getirilemez (HMK m. 350/2). İşe iade ilâmları da hemen icra edilemez ve şeklî anlamda kesin hüküm hâline gelmeden icra-ya konulmaz (İş Kanunu m. 21/6). İşçinin işe iadesi-ne hükmedilir fakat ilâmın koşulları ilâm borçlusu tarafından tam olarak yerine getirilmezse, işçi icra dairesine başvurmalı ve icra emri tebliğ ettirme-lidir. İşe iade ilâmı kendiliğinden kabili icra oldu-ğundan cebrî icraya muhtaç değildir. Buna karşılık işe iade ilâmındaki yargılama giderleriyle avukatlık ücretinin ilâmlı icraya konulması gerekir. İşe iade ilâmı derhal icra edilebilir olmadığında, ilâm ala-caklısı ilâmın şeklî anlamda kesinlik kazanmasına kadar beklemelidir.

f the employee is unfairly dismissed, he or she has the right to sue for reinstatement and also claim connected rights to obtain judicial order. The judgment granting the relief has the same le-gal effect as if a new labor contract is concluded. The employee who is unfairly dismissed can apply to labor court to obtain an order for his reinstate-ment. If the employee wins the lawsuit he or she can apply to enforcement offices in order to com-pel the judgment-obligee to the performance of the secondary issues in reinstatement judg-ment. According to the Code of Civil Procedure, application to appeal shall not stay the enforce-ment of the judgments. The provision in article 36 of the Code of Enforcement and Bankruptcy regarding stay of enforcement is reserved (CPC a. 350/1). Rulings regarding the law of persons, family law and property rights concerning real property shall not be enforced until they become unappealable (CPC a. 350/2). Also reinstatement judgments are not immediately enforceable and they shall not be enforced until they become res judicata effect (Labor Code a. 21/6). If an employ-ee is ordered to be re-instated or re-engaged but the terms of the judgment are not fully complied with by the judgment-obligee then the employ-ee must apply to enforcement offices and send an enforcement order. No enforcement is neces-sary for the reinstatement judgment because it is a self-executory judgment. However, the judicial costs and attorney fee which had been ordered in the reinstatement judgment are needed to be en-forced. When the reinstatement judgment is not immediately enforceable, the judgment-creditor must wait until the judgment becomes formal res judicata.
Formal Res Judicata Condition in Enforcement of Reinstatement Judgments